Adolescent pregnancy at antiretroviral therapy (ART) initiation: a critical barrier to retention on ART. Issue 9 (18th September 2018) - Nuwagaba‐Biribonwoha, Harriet; Kiragga, Agnes N; Yiannoutsos, Constantin T; Musick, Beverly S; Wools‐Kaloustian, Kara K; Ayaya, Samuel; Wolf, Hilary; Lugina, Emmanuel; Ssali, John; Abrams, Elaine J; Elul, Batya; ,
Abstract: Introduction: Adolescence and pregnancy are potential risk factors for loss to follow‐up (LTFU) while on antiretroviral therapy (ART). We compared adolescent and adult LTFU after ART initiation to quantify the impact of age, pregnancy, and site‐level factors on LTFU. Methods: We used routine clinical data for patients initiating ART as young adolescents (YA; 10 to 14 years), older adolescents (OA; 15 to 19 years) and adults (≥20 years) from 2000 to 2014 at 52 health facilities affiliated with the International epidemiology Databases to Evaluate AIDS (IeDEA) East Africa collaboration. We estimated cumulative incidence (95% confidence interval, CI) of LTFU (no clinic visit for ≥6 months after ART initiation) and identified patient and site‐level correlates of LTFU, using multivariable Cox proportional hazards models for all patients as well as individual age groups. Results: A total of 138, 387 patients initiated ART, including 2496 YA, 2955 OA and 132, 936 adults. Of these, 55%, 78% and 66%, respectively, were female and 0.7% of YA, 22.3% of OA and 8.3% of adults were pregnant at ART initiation. Cumulative incidence of LTFU at five years was 26.6% (24.6 to 28.6) among YA, 44.1% (41.8 to 46.3) among OA and 29.3% (29.1 to 29.6) among adults. Overall, compared to adults, the adjusted hazard ratio, aHR, (95% CI) of LTFU for OA was 1.54 (1.41 to 1.68) and 0.77 (0.69 to 0.86) for YA. Compared to males, pregnant females had higher hazard of LTFU, aHR 1.20 (1.14 to 1.27), and nonpregnant women had lower hazard aHR 0.90 (0.88 to 0.93). LTFU hazard among the OA was primarily driven by both pregnant and nonpregnant females, aHR 2.42 (1.98 to 2.95) and 1.51 (1.27 to 1.80), respectively, compared to men. The LTFU hazard ratio varied by IeDEA program. Site‐level factors associated with overall lower LTFU hazard included receiving care in tertiary versus primary‐care clinics aHR 0.61 (0.56 to 0.67), integrated adult and adolescent services and food ration provision aHR 0.93 (0.89 to 0.97) versus nonintegrated clinics with food ration provision, having patient support groups aHR 0.77 (0.66 to 0.90) and group adherence counselling aHR 0.61 (0.57 to 0.67). Conclusions: Older adolescents experienced higher risk of LTFU compared to YA and adults. Interventions to prevent LTFU among older adolescents are critically needed, particularly for female and/or pregnant adolescents.